1998
DOI: 10.1126/science.279.5352.837
|View full text |Cite
|
Sign up to set email alerts
|

A Rare-Earth Phosphor Containing One-Dimensional Chains Identified Through Combinatorial Methods

Abstract: An unusual luminescent inorganic oxide, Sr2CeO4, was identified by parallel screening techniques from within a combinatorial library of more than 25,000 members prepared by automated thin-film synthesis. A bulk sample of single-phase Sr2CeO4 was prepared, and its structure, determined from powder x-ray diffraction data, reveals one-dimensional chains of edge-sharing CeO6 octahedra, with two terminal oxygen atoms per cerium center, that are isolated from one another by Sr2+ cations. The emission maximum at 485 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 398 publications
(200 citation statements)
references
References 5 publications
(1 reference statement)
7
193
0
Order By: Relevance
“…A key advantage of the inkjet delivery system is that precursors can be mixed at the molecular level in the nozzle prior to controlled delivery at each site, thus avoiding the need for thermal interdiffusion treatment of the library. 183 In another study, 176 electron beam deposition in a moving shutter system was used to create a large library containing composition gradients of multiple phosphor hosts as well as different RE dopants, Fig. 47.…”
Section: -23mentioning
confidence: 99%
“…A key advantage of the inkjet delivery system is that precursors can be mixed at the molecular level in the nozzle prior to controlled delivery at each site, thus avoiding the need for thermal interdiffusion treatment of the library. 183 In another study, 176 electron beam deposition in a moving shutter system was used to create a large library containing composition gradients of multiple phosphor hosts as well as different RE dopants, Fig. 47.…”
Section: -23mentioning
confidence: 99%
“…These libraries were processed in air at temperatures from 900°C to 1100°C for 8 hours. The combinatorial libraries were characterized using a high throughput screen that illuminated the library with blue light to rapidly screen for potential hits 10,11 . A Ushio 200 W Hg/Xe lamp was used for illumination together with bandpass filters of 430, 450, and 465-nm (FWHM=25-35 nm) for phosphor excitation.…”
Section: Methodsmentioning
confidence: 99%
“…Our work employs combinatorial chemistry as a tool to rapidly generate libraries of garnet phosphors to examine the spectral trends in phosphors for application in blue to yellow conversion LEDs. Combinatorial methods for luminescent materials discovery have been used previously by several groups [8][9][10][11] . Various garnets of the formula, A 3-x B x C 5-y D y O 12 :Ce 3+ , where A, B = Y, Gd, Lu, La; C, D = Al, Ga, Sc; x and y = 0 to 1.0; and a Ce concentration of 1.0 mol% were synthesized and characterized.…”
Section: +mentioning
confidence: 99%
“…In these materials the optical transitions are based on a ligand-to-metal charge transfer (CT) from O 2-to Ce 4? [122,123]. It was found that the addition of Sn 4?…”
Section: Blue Phosphors-other Hostsmentioning
confidence: 99%